Impact of Exchange rate on Macro-Economic Indicators: Evidence from Asian Region - Khokhar, Saad Alam; Khan, Dr. Muhammad Yar; Khan, Dr. Abdul Qayuum (UW Journal of Management Sciences, 2023)
Purpose: The purpose of this study is to examine the Impact of exchange rate on Macro-Economic Indicators. Design and Methodology: For this study data was collected from different source such as World development Indicator, International Statistic among others. Partial Least Square analysis has been used on data from 2005 to 2020 for Asian Countries. Findings: The results indicates that trade is more significant than FDI in Asian regions. More specifically, trade has a significant relationship while FDI has no significant relationship in Asian Countries. However, both variables have a significant relationship with exchange rate in case of Pakistan. Implications: The world is constantly facing the rapid downturn after covid-19 pandemic, this downturn has abruptly affected the investors’ sentiments to invest in underdeveloped countries. The study will facilitate the policy makers in formulation of new economic policies. In order to increase inflow of FDI and international trade, it is beneficial to have lowest exchange rate fluctuations. Further, the investors and traders can design their strategies by considering the fluctuation in exchange rate of these countries.